Central mechanisms of pathological pain - Kuner, Rohini (Nature medicine, 2010)
Chronic pain is a major challenge to clinical practice and basic science. The peripheral and central neural networks that mediate nociception show extensive plasticity in pathological disease states. Disease-induced plasticity can occur at both structural and functional levels and is manifest as changes in individual molecules, synapses, cellular function and network activity. Recent work has yielded a better understanding of communication within the neural matrix of physiological pain and has also brought important advances in concepts of injury-induced hyperalgesia and tactile allodynia and how these might contribute to the complex, multidimensional state of chronic pain. This review focuses on the molecular determinants of network plasticity in the central nervous system (CNS) and discusses their relevance to the development of new therapeutic approaches.